2020
DOI: 10.2147/cmar.s240000
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA CDKN2B-AS1 Promotes Cell Viability, Migration, and Invasion of Hepatocellular Carcinoma via Sponging miR-424-5p</p>

Abstract: Objective: Hepatocellular carcinoma (HCC) results in high mortality and metastasis. In this study, the effects of long non-coding RNA (lncRNA) CDKN2B-AS1 on the progression of HCC were investigated. Materials and Methods: LncRNA CDKN2B-AS1 expression of HCC cancer and adjacent tissues, and HCC cells were detected. Subsequently, CDKN2B-AS1 was overexpressed and silenced in HCC cells to observe the effects of CDKN2B-AS1 on the cell viability, migration, invasion, and epithelial-mesenchymal transition (EMT) of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…These target genes generally exert a protumor activity by promoting proliferation, migration, or angiogenesis in cancer cells. A few lncRNAs have been found to regulate miR-424-5p in various cancer cells, including LINC00922 in breast cancer [ 39 ], CDNK2B-AS1 in hepatocellular carcinoma [ 40 ], and XIST in neuroendocrine tumors [ 41 ]. In all the aforementioned cases, regulation of miR-424-5p by the corresponding lncRNA resulted in cell proliferation or cancer-progression alterations.…”
Section: Discussionmentioning
confidence: 99%
“…These target genes generally exert a protumor activity by promoting proliferation, migration, or angiogenesis in cancer cells. A few lncRNAs have been found to regulate miR-424-5p in various cancer cells, including LINC00922 in breast cancer [ 39 ], CDNK2B-AS1 in hepatocellular carcinoma [ 40 ], and XIST in neuroendocrine tumors [ 41 ]. In all the aforementioned cases, regulation of miR-424-5p by the corresponding lncRNA resulted in cell proliferation or cancer-progression alterations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that CDKN2B-AS1 is highly expressed in various cancer types and serves as an oncogenic factor by regulating multiple cellular events such as apoptosis [ 136 , 137 ]. Further evidence showed that CDKN2B-AS1 interacts with miR-411–3p, which directly targets HIF-1α in ovarian cancer [ 138 ].…”
Section: Lncrnas Regulating Hif-1α Expressionmentioning
confidence: 99%
“…LncRNAs have also been implicated in stem cell maintenance and differentiation, cell autophagy and apoptosis, and embryonic development ( Qian et al, 2019 ). The expression of specific lncRNAs is altered in many cancers, suggesting that lncRNAs contribute to tumorigenesis and/or tumor cell function ( Xia et al, 2019 ; Qi-Dong et al, 2020 ; Shen et al, 2020 ; Ren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%